Ação do inibidor de calicreína em linhagens de câncer de próstata - Ferreira, Joana Gasperazzo [UNIFESP] (2011)
Prostate cancer is the second more frequent type of cancer. In this work, using DU145 and PC3 prostate cancer cellular lines, we studied the effect of recombinant kallikrein inhibitor modified form (rBbKm), in which the sequence containing the signal motif sequence RGD of the inhibitor BrTI from Bauhnina rufa was inserted. When DU145 and PC3 were incubated with rBbKIm for 48h, and the conditioned medium the culture was incubated with the HD-Pro-Phe-Arg-ñNa, an kallikrein substrate, inhibited 95% of the degradation of this in both cells. rBbKIm inhibited cell viabillity of DU145 (56%, 100 ìM, 48 h) and PC3 (28%, 100 ìM, 48 h), but affect only 5% of the viabillity of fibroblast normal cell line (100 ìM, 48h). In cell adhesion, rBbKIm did not inhibit DU145 and PC3 cell line adhesion on fibronectin, laminin, collagen I and IV coat. In cell migration, rBbKIm did not inhibit DU145, but inhibited 38% of the PC3 (100 ìM) after 23 h. To evaluate the cytotoxicity, DU145 and PC3 were incubated with rBbKIm (50 and 100 ìM, 24 and 48h) inducing cell death by apoptosis. The presence of rBbKIm arrest PC3 cell cycle at the G0/G1 and G2/M phase, but did not affect DU145. Both cells released cytocrome c to the cytosol when treated with rBbKIm (50 and 100 ìM) for 24h. Moreover, DU145 when was treated with rBbKIm for 48h activated the caspase-3. However PC3 did not activated caspase-3, but activated caspase-9. The peptides containing the RGD and RGE sequence did not inhbit the cell viabillity of DU145 and PC3. Analyzing the effect of rBbKIm on HUVEC viabillity and migration, rBbKIm (50ìM) inhibited 28% and 30%, respectively. This protein inhibited 49% of the HUVEC angiogenesis in vitro on Matrigel. In summary, we have demonstrated the differential action of the protease inhibitor rBbKIm on androgen-independent prostate cancer PC3 and DU145, normal fibroblast and endothelial HUVEC cells.